Successful Kidney Transplant from Methanol-Intoxicated Donors. (June 2014) - Sklienka, Peter; Neiser, Jan; Ševčík, Pavel; Dvořáček, Igor; Samlík, Jiří; Jonszta, Tomáš; Dedek, Vladimír; Kubišová, Michaela Matyskov; Tomanová, Radoslava; Streitová, Dana
The well-described disparity between the need for and the supply of organs suitable for transplant is growing. Because of this disparity, mortality of patients listed for transplant is increasing. Donors who die of intoxication (including victims of methanol poisoning) represent less than 1% of suitable donors and might be used to increase the supply of organs. They are often not accepted as donors by transplant specialists, because of concerns about patients' outcomes with these grafts. Three cases of fatal methanol intoxication that resulted in transplants of 6 kidneys are evaluated.